Investigation of Human Awareness on Solid Waste Management at Taman Seroja and Data Collection in Sik, Kedah - Baharom, Nur Farhana; Kasmin, Hartini (Recent Trends in Civil Engineering and Built Environment, 2024)
Abstract: Nowadays, solid waste generated in Malaysia is increasing in line with urbanization and population growth. The increasing of population together with the increasing in economic status has led to an increasing in the amount of solid waste generation in Sik, Kedah. Typical problem occurs in most residential areas when they were unable to effectively manage the solid waste on practicing the separation method. Therefore, the objectives of this study are to review and identify the effect of improper solid waste management in Malaysia, to identify the human awareness on waste separation in a residential area and to analyze the changes rate of solid waste before and during Movement Control Order (MCO) in Sik, Kedah. It has been identified that from the previous studies, improper management could impact on two main issues which are on environment such as water and air pollution; and flood due to clogging; whilst impact on human will cause disease such as dengue, leptospirosis and salmonella. In order to understand the human awareness, based on the survey conducted, 32 respondents (58%) of the 50 respondents (100%) were not agree in participating in recycling activities due to time consuming to separate the wastes. In addition, it is found that when comparing the changes rate of solid waste due to MCO, 7% of solid waste increment during MCO compare to year before MCO in 2019 with highest increment differences on months of April and May at 15% and 23%, respectively. This result shows that each resident did produced more wastes when they work from home, when they can only litter from their home only. As a conclusion, this study indicates that solid waste management can be effectively executed when all parties play their roles to achieve better management.